2014
DOI: 10.5902/2316546416507
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento Tático Declarativo Em Jogadores De Futebol Sub-14 E Sub-15

Abstract: Este artigo comparou o Conhecimento Tático Declarativo (CTD) de jogadoresde Futebol das categorias sub-14 e sub-15. Utilizou-se o teste de Mangas, com cenasde vídeo previamente validadas, aplicando-o em 26 atletas do sexo masculino (16 atletassub-15 e 10 atletas sub-14). Os dados foram analisados através do Median Test. Atletasda categoria sub-15 apresentaram CTD significativamente superior aos atletas sub-14,revelando que o tempo de prática apresenta-se como importante no desenvolvimento doCTD de jogadores de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…For Giacomini et al, 32 the practice time that athletes accumulate in a modality directly influences their level of declarative tactical knowledge. In this sense, the comparison of declarative tactical knowledge among soccer players of the U-14 and U-15 categories suggested that older athletes (U-15 category) had significantly better knowledge than younger athletes (U-14) 33 . This information indicates that the time of practice is determinant for the development of declarative tactical knowledge in soccer players.…”
Section: Discussionmentioning
confidence: 94%
“…For Giacomini et al, 32 the practice time that athletes accumulate in a modality directly influences their level of declarative tactical knowledge. In this sense, the comparison of declarative tactical knowledge among soccer players of the U-14 and U-15 categories suggested that older athletes (U-15 category) had significantly better knowledge than younger athletes (U-14) 33 . This information indicates that the time of practice is determinant for the development of declarative tactical knowledge in soccer players.…”
Section: Discussionmentioning
confidence: 94%
“…In soccer, the findings show that the time of practice from 4.5 years leads to better DTK score of 48 athletes from two U-17 category teams 6 . Also in soccer, the DTK level was higher for U-15 categories when compared to the U-14 7 category and, in relation to age, 20-year-old athletes were superior to those of lower ages 8 .…”
Section: Introductionmentioning
confidence: 86%
“…Nos estudos previamente citados observam-se resultados inconclusivos sobre quais são as variáveis independentes que determinam baixos e/ou altos níveis de CTD nos atletas. Dentre as variáveis frequentemente citadas verificou-se que os melhores níveis de CDT foram encontrados para os atletas com mais tempo de prática na modalidade (MOREIRA et al, 2014;SANTOS;MACHADO, 2017;IROKAWA et al, 2011), entretanto, em outros estudos estes resultados não foram encontrados (COSTA;MIZAEL;REYES, 2015;SILVA et al, 2018;CARÍSSIMO, 2021). Quanto a variável idade, observou-se que os praticantes das categorias mais velhas apresentam melhor conhecimento tático em relação às categorias mais novas (MOREIRA et al, 2014;DOS SANTOS;MACHADO, 2017;IROKAWA et al, 2011), e os melhores colocados em competições são os atletas que apresentam melhor nível de CTD (SILVA et al, 2014;RODRIGUES et al, 2017).…”
Section: Introductionunclassified